Clinical characteristics of 26 patients with primary extranodal Hodgkin lymphoma - Ma, Jing (e-Century Publishing Corporation, 2014)
Background: Most Hodgkin lymphoma (HL) patients present with disease in nodal regions. However, in a small subset, disease develops extranodal sites primarily, such as lung and liver. This study aims to identify the characteristics and outcomes of patients with primary extranodal HL. Methods: A retrospective analysis of patients with HL from 1998 to 2012 was enrolled. We selected 26 HL patients with primary extranodal involvement from 251 previously untreated HL patients. All data analyses were performed with SPSS software version 17.0 and GraphPad Prism 5. Results: We identified 26 patients with primary extranodal HL. Results in the series of young patients, male predominated. Pathologically, the major pathologic types were nodular sclerosis classical HL (NSCHL, 46.2%) and mixed cellularity classical HL (MCCHL, 38.5%). Thirteen patients had early stage (I or II stage). The most commonly primarily extranodal sites were the lung and the stomach and intestine, followed by the liver and bones. Fifteen of 26 received chemotherapy alone and 11 received combination therapy. Finally, primary extranodal HLs in our study have a favorable survival. Furthermore, there was no significant association between the international prognostic score (IPS) and survival in patients with extranodal HL. Conclusion: Our retrospective data in part reflect clinical characteristics of primary extranodal HL in China, and form the basis for further concerning researches.